Poly(N-‎vinylimidazole): A ‎biocompatible‎, efficient, and ‎highly ‎‎recyclable ‎heterogeneous ‎catalyst for ‎the ‎preparation of ‎bis(3-‎‎indolyl)methanes ‎ - Gorjian, Hayedeh; Fahim, Hoda; Khaligh, Dr. Nader Ghaffari (Malaysian Catalysis-An International Journal, 2021)
Poly(N-vinylimidazole) (PVIm), as a biocompatible, efficient, halogen-free, and reusable catalyst, was ‎applied for the solvent-free synthesis of a library of bis(3-indolyl)methanes. The reaction was ‎smoothly carried out under mild conditions, and the crude products were purified easily, and ‎the pure products were obtained in high to excellent yields.‎